THE INTERPLAY OF TRUST: MEDIATING AND MODERATING EFFECTS IN THE COMMUNICATION-LOYALTY RELATIONSHIP IN PRIVATE HOSPITALS IN VIENTIANE - Louangpradith, Chanthavikhone; Ratasuk, Akaraphun (Chinese Journal of Social Science and Management, 2026)
Purpose: This study investigated the relational mechanisms linking communication eﬀectiveness to patient loyalty within the private healthcare sector of Vientiane, Lao PDR. Rooted in the Social Exchange Theory (SET), the research specifically examined trust’s mediating and moderating role in translating service communication into behavioral commitment. Study Design/Methodology/Approach: A quantitative research design involved a self-administered online questionnaire to gather data from 512 patients who had recently used private hospital services in Vientiane. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to evaluate the measurement and structural models. Findings: The results oﬀered strong empirical evidence of the direct eﬀect of communication eﬀectiveness on patient loyalty (β = 0.252, p < 0.001). Furthermore, the study identified trust as a critical mechanism: communication eﬀectiveness significantly drives trust (β = 0.778, p < 0.001), which in turn boosts loyalty (β = 0.550, p < 0.001). Mediation analysis confirms that trust functions as a crucial partial mediator (β = 0.428, p < 0.001). However, the hypothesized moderating eﬀect of trust was not significant (β = -0.002, p = 0.478), indicating that trust serves as a fundamental prerequisite rather than a conditional buﬀer in this high-risk context. Originality/Value: This research advances SET by conceptualizing trust’s dual role in a transitional Southeast Asian economy. It challenges Western-centric models by showing that, in the Lao PDR’s developing healthcare market, trust acts as a “hygiene factor” essential for the relationship to exist, but does not amplify service inputs.